Photolysis of sodium chloride and sodium hypochlorite by ultraviolet light inactivates the trophozoites and cysts of Acanthamoeba castellanii in the water matrix - Beni J. M. Chaúque (IWA Publishing, 2021)
The present study aimed to investigate an effective, sustainable and accessible way to inactivate chlorine-resistant microorganisms, such as Acanthamoeba castellanii, through the photolysis of sodium chloride (NaCl) and sodium hypochlorite (NaOCl) in the water matrix. The trophozoites and cysts (2 × 107 per 8 mL) were exposed for 30, 60, 90, 120 and 150 min to the photolysis effect of NaOCl (1.0, 2.0, 4.0 and 8.0 mg/L) or NaCl (5.0, 10, 20 and 40 g/L) by ultraviolet light C (243 μW·cm2), then the viability was analyzed. The inactivation of all trophozoites was achieved by exposure to the photolysis effect of 2.0 mg/L of NaOCl or 20 g/L of NaCl, in 150 or 120 min, respectively. Inactivation of all cysts was achieved by double exposure to the photolysis effect of 1.0 mg/L NaOCl or 5.0 g/L NaCl from 90 min of each exposure round. The exposure time was a strong determinant in the inactivation of A. castellanii trophozoites or cysts. The photolysis of NaOCl or NaCl is an effective method to eliminate A. castellanii in water. These findings expand the list of chlorine-resistant microorganisms that can be inactivated by NaOCl photolysis and show that NaCl photolysis is a new and promising method for treating swimming pool water and wastewater.